Knowledge, Attitude, and Practice toward Skin Cancer Prevention and Detection among Jordanian Medical Students: A Cross-Sectional Study - Khaled Seetan; Almu’atasim Khamees; Afnan Migdadi; Mosab Abu Shqeer; Maram Jameel Hasan; Leen Ahmad Shatnawi; Tala Abu Bakr; Nada Zayed (Journal of Skin Cancer)
Introduction. Skin cancer is one of the most growing types of cancer, especially in the Mediterranean, even though it is a preventable disease. The purpose of this study is to assess medical students’ knowledge, attitude, and practice about skin cancer prevention and detection. Methods. A cross-sectional study was conducted using a validated structured questionnaire covering the areas of knowledge, attitude, and practice of the study participants. Results. The study involved 1530 students; 55.3% were females. Most of the students possessed proper knowledge about skin cancer (81%). The most prevalent skin cancer risk factors were sun exposure during the day (83.5%) and immunosuppression (71.2%). More than half of the students did not have any habits of skin examination (61.5%). 20% of the students never used sunscreen, while only 20% of them avoided sun exposure during day hours. Conclusion. The general level of the medical students’ knowledge of skin cancer and its risk factors appeared to be higher than what is found in other studies; it is reasonable as the study participants were medical students. However, the protective behavior from the sun was inadequate when compared to the level of knowledge reported. Additional education about the behavior toward sun exposure and protection against skin cancer may be needed to be implemented in the dermatology curriculum.